2004
DOI: 10.1212/01.wnl.0000142424.65251.db
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of the hypocretin receptor 2 gene is associated with cluster headache

Abstract: Several polymorphisms of the hypocretin/orexin system genes were evaluated in 109 cluster headache patients and 211 controls. The 1246 G>A polymorphism of the gene was significantly different between cases and controls. Homozygosity for the G allele was associated with an increased disease risk (OR: 6.79, 95% CI, 2.25 to 22.99). The data suggest that the HCRTR2 gene or a linked locus significantly modulates the risk for cluster headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 9 publications
2
104
1
Order By: Relevance
“…We have recently shown that the G1246A polymorphism of the HCRTR2 gene is significantly associated with CH [14]. This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15].…”
Section: Introductionmentioning
confidence: 56%
“…We have recently shown that the G1246A polymorphism of the HCRTR2 gene is significantly associated with CH [14]. This association was confirmed by a large study performed in Germany, showing that homozygous carriers of the G allele had a twofold increase in risk for the disease [15].…”
Section: Introductionmentioning
confidence: 56%
“…Clinical studies have identified polymorphisms within the orexin receptor genes that are associated with cluster headache and migraine. A 1246G3 A polymorphism in HCRTR2 is significantly associated with cluster headaches but not with treatment response, whereas the same polymorphism is not associated with migraine (Rainero et al, 2004Schü rks et al, 2006Schü rks et al, , 2007aPinessi et al, 2007). More recently, a 1222G3 A polymorphism within the HCRTR1 gene has been found to be associated with an increased risk of migraine without aura (Rainero et al, 2011).…”
Section: B Orexin Influences On Peripheral Physiologymentioning
confidence: 99%
“…A polymorphism of the hypocretin receptor 2 gene has recently been associated with CH [3], a remarkable association since hypocretin-containing cells are located exclusively in the posterolateral hypothalamus. A striking feature of CH is its diurnal and seasonal periodicity, suggesting that circadian and infradian rhythms regulate CH attacks.…”
mentioning
confidence: 99%